The Developing a Fiqh Student Worksheet Based on Problem-Based Learning to Improving Critical Thinking Skills - Br Purba, Risma; Sinaga, Ali Imran; Haidir (JIE (Journal of Islamic Education), 2024)
The urgency of this research is developing (Problem Based Learning) PBL Student Worksheets to improve fiqh learning in schools, improve students' critical thinking skills and reduce the gap between theory and practice. This research aims to develop a PBL-based Student Worksheet to enhance students' critical thinking skills in fiqh, focusing on design, implementation and evaluation of its impact. This research is R&D research that develops a PBL-based fiqh Worksheet by adopting the Four-D Model, which includes the define, design, develop, and disseminate stages, to ensure a systematic and practical instructional development process. The development of PBL-based student worksheets that consider learning needs and PBL syntax and are validated by experts has improved student learning outcomes, as evidenced by increased N-Gain scores and more active student participation in learning. The limitations of this research include the focus on one school as a sample, as well as limited time for implementing PBL-based Student Worksheets, while the implications emphasise the importance of developing innovative learning methods and continuous support from educational stakeholders to expand the application of PBL-based learning models in learning fiqh. This research proposes a systematic approach to developing Fiqh Worksheets with PBL, starting from identifying challenges to testing and increasing their effectiveness, which contributes to increasing student engagement and learning outcomes, as well as critical thinking skills through proven PBL-based Student Worksheets in the N-Gain test results.